PERLINDUNGAN HUKUM TERHADAP PENGUSAHA KERAJINAN TENUN SEBAGAI PENDORONG PEREKONOMIAN SUMATERA BARAT - Andalusia, Andalusia; Nurfirmansyah, Nurfirmansyah (Jurnal Hukum Bisnis Bonum Commune, 2022)
Songket Weaving is one of the local cultural wisdoms for cloth products that have distinctive characteristics from West Sumatra. In fact, in the field, the benefits of songket woven fabric will become a regional characteristic so that it can increase the presence of products from West Sumatra, both nationally and internationally. The process of preserving the uniqueness and wisdom of local culture certainly requires optimization from the parties. Registration of Trademarks and Geographical Indications is very important to protect traditional products in each region. Intellectual Property Rights regulate Trademark Rights and Geographical Indications where the number of handicraft products from the region is countless. This legal research method is Juridical Empirical with descriptive and analytical approach. The results of this study are that the protection of West Sumatran songket handicraft business actors has been registered since 2018 on songket weaving from Silungkang, Sawahlunto. But the woven fabric from Balai Panjang, Payakumbuh is still registering the motif through copyright. Second, the role of the Regional Government continues to encourage the wisdom of local business actors through socialization, promotion, education, to registration with the Director General of Intellectual Property Rights so that no other party can admit it without the permission of the trade right holder. Such as the establishment of a woven fabric center in Balai Panjang, Payakumbuh and the existence of SK No.188.45/37/WAKO-SWL/2019 as a supervision of silungkang woven fabric products on the geographical indication rights